ISLAMIC BOARDING SCHOOL MANAGEMENT IN OVERCOMING BULLYING IN THE KABUPATEN DELI SERDANG ISLAMIC BOARDING SCHOOL - Muhammad Rizki Dermawan Saragih; Mara Samin; Inom Nasution (Research and Development Journal of Education, 2023)
This research aims to examine the management of Islamic boarding schools in addressing bullying in Deli Serdang Regency. The study includes understanding the planning, organizing, implementing strategies, controlling, as well as the factors causing and the constraints in addressing bullying. This research adopts a qualitative descriptive approach, with data collection through observation, interviews, and documentation based on predetermined criteria. The collected data are analyzed through data collection, data reduction, data presentation, conclusion drawing, and data verification. The findings of the research indicate that the management of Islamic boarding schools employs strategic measures, such as separating dormitories, implementing the "Father Sponsor" program, collaborating with local police, improving regulations, instilling Islamic values, and fostering student organizations. Each step and strategy are implemented through the processes of planning, organizing, implementing, and controlling to achieve the established goals. The factors causing bullying behavior in Islamic boarding schools in Deli Serdang Regency include power dynamics and hierarchy within the school, social incompatibility, external environmental influences, diverse backgrounds, lack of understanding of the consequences of bullying, a desire for superiority, and dissatisfaction or non-acceptance of the situation. The barriers in addressing bullying include the lack of fear from the perpetrators, reluctance of victims to report incidents due to shame, inadequate sanctions, and the time required to instill Islamic values.